Phenolic content and lipid quality of nuts of baru fruits submitted to pest management and stored at different temperatures - MENDONÇA, Jenifer da Silva; GUIMARÃES, Rita de Cássia Avellaneda; SANTANA, Lidiani Figueiredo; POTT, Arnildo; CAVALHEIRO, Leandro Fontoura; NAZÁRIO, Carlos Eduardo Domingues; HIANE, Priscila Aiko; NASCIMENTO, Valter Aragão do; BOGO, Danielle; DONADON, Juliana Rodrigues (Food Science and Technology, 2024)
Baru is a fruit produced only once a year which requires adequate planning of seasonal maintenance to maintain the quality of its nut for consumption. This study aimed to evaluate the effect of hydrothermal treatment on pest control and temperature and storage time on baru fruits on the phenolic content and the lipidic quality of the nuts. We stored the fruits at ambient temperature (29°C) and climatized at 18°C. We evaluated them at 0, 60, 120, and 180 days for insect damage, water content, total phenols, tannins, antioxidant activity, lipid profile, acidity, peroxide and iodine indices, and oxidative stability by Rancimat. The integrated management was efficient in pest control, and nuts extracted from fruits preserved the bioactive compounds independently of storage temperature and presented chemical characteristics acceptable for consumption. The fatty acids found in higher proportions in baru nuts were oleic (50%) and linoleic acids (27%) and remained preserved over time. Thus, it promotes the supply of oilseeds to the market with consistency and quality between crops, avoiding unnecessary losses during storage.